Recycling and disposal of battery materials - Smith, Michael John (2016)
Portable electronic devices that rely on batteries as a source of power have rapidly evolved to become essential accessories of everyday life and whether the device in question is a remote-control command, a child´s toy, a smart-phone/organiser or a laptop computer, it relies on its battery-pack to provide a source of continuous electrical power. In many cases the efficiency of these batteries also largely determines the commercial success of the device. While the batteries applied in this equipment safely contain their chemical components during normal use, inappropriate disposal at the end of their working lifetime can result in the release of toxic chemicals to the environment. The consequences of disposal of a wide variety of battery types to landfill sites or municipal incinerators instead of responsible chemical neutralization and recovery of active components, have led battery producers and vendors, legislators and the consumer population to recognize the need to introduce improved procedures and battery recycling has become a priority on the environmental and political agenda.